A broadband absorptive filtering antenna and its application in a 5G multi‐input multi‐output array. Issue 9 (28th May 2022) - Li, Hua; Lee, Zong‐Ze; Xi, Hai‐Qing; Kang, Bo‐Xiong; Jing, Dai‐Bing; Ding, Xiao
Abstract: To meet the needs of 5G communication and protect power amplifiers from the reflected energy interference, a broadband absorptive filtering antenna (AFA) covering N77 band (3.3–4.2 GHz) is designed, and further applied to a multi‐input multi‐output (MIMO) array. The presented AFA element realizes a wide range of reflectionless all‐pass characteristics by establishing an absorptive branch. The independently adjustable operating band and absorptive stopband are obtained by using a filtering structure and a defective ground structure (DGS) structure respectively. When the transfer functions of the radiative channel and the absorptive channel are complementary, the proposed AFA element achieves a reflectionless bandwidth of 2.55–5.05 GHz (65%) and an average gain in the operating band of 8.3 dBi. Unlike traditional antennas that reflect the stop‐band energy, the AFA element dissipates the stop‐band reflected energy, which can effectively reduce the correlation of the MIMO elements, thereby improving the radiation performance of the MIMO antenna. Simulation and measurement results show that the MIMO antenna composed of the proposed AFA elements achieves in‐band average gain of 7.4 dBi, port isolation of more than 24 dB, out‐of‐band suppression more than 20.1 dB, and extremely low envelope correlation coefficient (ECC) less than 2 × 10 −4 due to the unique out‐of‐band reflectionless filtering characteristics of the AFA element.